Poor relationship between arterial [lactate] and leg net release during exercise at 4,300 m altitude - Brooks, G. A.; Wolfel, E. E.; Butterfield, G. E.; Cymerman, A.; Roberts, A. C.; Mazzeo, R. S.; Reeves, J. T. (American Journal of Physiology - Regulatory, Integrative and Comparative Physiology, 1998)
We evaluated the hypotheses that on acute exposure to hypobaric hypoxia, sympathetic stimulation leads to augmented muscle lactate production and circulating [lactate] through a -adrenergic mechanism and that -adrenergic adaptation to chronic hypoxia is responsible for the blunted exercise lactate response after acclimatization to altitude. Five control and 6 -blocked men were studied during rest and exercise at sea level (SL), on acute exposure to 4,300 m (A1), and after a 3-wk sojourn at altitude (A2). Exercise was by leg cycling at 49% of SL peak O2 consumption (O2 peak) (65% of altitude O2 peak or 87 ± 2.6 W); -blockade was by propranolol (80 mg 3× daily), femoral arterial and venous blood was sampled; leg blood flow () was measured by thermodilution, leg lactate net release [ = (2) (1-leg Q) venous-arterial concentrationL] was calculated, and vastus lateralis needle biopsies were obtained. Muscle [lactate] increased with exercise and acute altitude exposure but regressed to SL values with acclimatization; -blockade had no effect on muscle [lactate]. Arterial [lactate] rose during exercise at SL (0.9 ± 0.1 to 1.5 ± 0.3 mM); exercise at A1 produced the greatest arterial [lactate] (4.4 ± 0.8 mM), and exercise at A2 an intermediate response (2.1 ± 0.6 mM). -Blockade reduced circulating [lactate] ~45% during exercise under all altitude conditions. increased transiently at exercise onset but then declined over time under all conditions. Blood and muscle "lactate paradoxes" occurred independent of -adrenergic influences, and the hypotheses relating the blood lactate response at altitude to -adrenergic mechanisms are rejected. During exercise at altitude, arterial [lactate] is determined by factors in addition to hypoxemia, circulating epinephrine, and net lactate release from active muscle beds.